(3CSGSjGJ GdEbJUGO GdQjGVjs - (3MSjf Ydj(B, (3HNjJs; (3ZGdH YhV GdQaGYj(B, s ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2002)
(3GdEWGQ GdeaGgjej(B-(3JhGRf GdShb(B-(3JhGRf GdONd(B-(3GSJNOGe GdeSahaGJ aj Md GdJhGRf(B-(3fehPL GdeSJNOe GdefJL(B-(3Gdejd hGdeQhfI aj GdOhGd GdEbJUGOjI(B-(3GdCeKdjI ddOhGd GdEbJUGOjI PGJ GdeJZjQ GdhGMO(B-(3GdCeKdI ddOhGd GdEbJUGOjI PGJ GdeJZjQGJ GdeJYOOI(B-(3OhGd GdEfJGL(B-(3GdHQeLI GdNWjIs
Keywords: (3GdEbJUGO GdQjGVjs; (3GdOhGds